Exploring grip strength as a predictor of depression in middle-aged and older adults - Marques, Adilson (2021)
Grip strength (GS) is an indicator of health and vulnerability and inversely associated with depressive symptoms. The aim of this study was to explore GS discrimination capacity for depression; and possible GS cut-of values for depression by sex and age group. Data from 2011 and 2015 on 20,598 (10,416 women) middle-aged and older adults from 14 European countries was analysed. GS was assessed by dynamometer, and depressive symptoms using the EURO-D scale. GS cut-of values for depression were calculated and logistic regression models were used to quantify the odds of having depression in 2011 and in 2015 according to being bellow or above the cut-of value. GS had a weak discriminant capacity for depression, with the area under the curve varying between 0.54 and 0.60 (p < 0.001). Sensitivity varied between 0.57 and 0.74; specifcity varied between 0.46 and 0.66. GS cut-of values for discriminating depression were 43.5 kg for men and 29.5 kg for women aged 50–64 years, 39.5 kg for men and 22.5 kg for women aged≥ 65 years. Having GS above the cut-of represents signifcant lower odds of depression in 2011 and 4 years later, in 2015. Healthcare practitioners and epidemiologic researchers may consider the low GS cut-of values to screen for potential depression risk. However, due to its weak discriminant values these cut-ofs should not be used to identify depression.